The Global South in a Multipolar World Order: - Virdika Rizky Utama (Journal Of Global Strategic Studies, 2025)
In the context of the Global South, this research examines the dynamics of relations between Indonesia and China, with a particular emphasis on economic cooperation, diplomacy, and geopolitical influence. This research primarily examines the impact of the Indonesia-China strategic partnership on the economic development of Indonesia and the ASEAN region, as evidenced by initiatives such as the Belt and Road Initiative (BRI). It also examines the potential economic dependency and geopolitical conflict in the South China Sea and the implications of this cooperation for developing countries. This study concludes that the Indonesia-China partnership can serve as a model of South-South collaboration that contributes to a more equitable multipolar global order. However, it necessitates strategic balance to prevent over-dependence. This conclusion is reached through a qualitative approach.